Public Administration And Sustainable National Development In Nigeria’s Fourth Republic - Ighodalo, Akhakpe (Advances in Social Sciences Research Journal, 2018)
Public administration is popularly regarded as the handmaid of public policies. However, this traditional role of public administration has since changed. Public administrators now play vital roles in policy formulation as the perceived gap between politics and administration continue to close up. Yet, since independence, national development has progressed in twists and turns thereby necessitating the imperative of sustainable national development. In the quest for sustainable national development, public administration is certainly a game changer. Therefore, with the use of the ecological theory, the paper argued that in the quest for sustainable national development in the country, there are stumbling blocks before public administration which should be surmounted. These include among others: lack of ethical climate in the public sector, poor professionalization of public administration, lack of inclusive decision making, attitudinal change by public officers, pursuit of foreign paradigm of development, lack of merit system in the public sector and low morale among public administrators. The paper made far-reaching recommendations on how to achieve sustainable national development through public administration. These include: comparative pay and reward system, ability to develop home grown development paradigm, reliable power supply, training and retraining of public officers, emphasis on merit and zero tolerance to corruption.